Approximation of the Conjugate of a Function Belonging to the Means of the W (Lᴾ , ξ (t)) Class by (N, Pₙ) (E, 1) Conjugate Series of the Fourier Series - Dhakal, Binod Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2009)
In this paper, a theorem concerning the degree of approximation of the conjugate of a function belonging to W (Lᴾ , ξ (t)) Class by (N, Pₙ) (E, 1) means of its conjugate series of a Fourier series has been proved.